2011
DOI: 10.1016/j.actamat.2011.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Study of the twinned dendrite tip shape I: Phase-field modeling

Abstract: The growth kinetics advantage of twinned aluminum dendrites over regular ones is still an unsolved problem of solidification. Although it is linked to the tip geometry, the influence of a coherent (1 1 1) twin plane on a h1 1 0i twinned dendrite tip is unclear, despite several past experimental observations. In the present contribution, a three-dimensional phase field model implemented on a cluster of parallel computers has been used to simulate the growth of a twinned dendrite under various directional solidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…This last profile shows no sign of positive segregation near the dendrite trunk center, in agreement with our previous observations [6]. Indeed, considering a diffusion coefficient in the solid of about 3 Â 10 À12 m 2 s À1 and a doublon inner pool a few microns wide (see [10]), back-diffusion at high temperature occurs only within a few seconds and can therefore smear out any slight positive segregation within this region. On the other hand, the composition profile (A) measured along the twin plane reveals a slight solute increase as one moves closer to the tip.…”
Section: Observations Of "Self-quenched" Twinned Dendrite Tipssupporting
confidence: 77%
See 3 more Smart Citations
“…This last profile shows no sign of positive segregation near the dendrite trunk center, in agreement with our previous observations [6]. Indeed, considering a diffusion coefficient in the solid of about 3 Â 10 À12 m 2 s À1 and a doublon inner pool a few microns wide (see [10]), back-diffusion at high temperature occurs only within a few seconds and can therefore smear out any slight positive segregation within this region. On the other hand, the composition profile (A) measured along the twin plane reveals a slight solute increase as one moves closer to the tip.…”
Section: Observations Of "Self-quenched" Twinned Dendrite Tipssupporting
confidence: 77%
“…As presented in the companion paper [4], three conjectures have been put forward for the tip shape of h1 1 0i twinned dendrites in order to explain their growth advantage over regular h1 0 0i dendrites in Al alloys: (i) a dendrite tip with a groove that is required to satisfy the Smith equation at the triple line between the twinned solid, the untwinned solid and the liquid [1]; (ii) a dendrite tip split in its center by a thin liquid pool, also called a doublon, due to solute pile-up ahead of a grooved tip [2]; and (iii) an edgy tip with consideration of torque terms induced by the anisotropy of the solid-liquid interfacial energy c s' [3]. An edgy tip would definitely give a growth advantage to twinned dendrites over regular ones, but this shape is incompatible with the very weak anisotropy measured recently for c s' in Al-Cu alloys [5].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…More confusion has been brought recently by Li et al [13], who observed that the application of a static magnetic field of only 0.2 T, which is supposed to weaken convection, induces the formation of twinned dendrites in Al-Fe and Al-Zn alloys in small DC cast ingots. Finally, although twinned dendrites have a growth advantage over regular dendrites under the above-mentioned conditions, there is still some uncertainty about their tip morphology [3,12,[14][15][16][17][18]. More important, nothing is known about twin nucleation.…”
Section: Introductionmentioning
confidence: 99%